Modeling a storage tank of carbon capture technology in a power plant in southern Iraq - Mustafa M. Mansour; Alaa M. Lafta; Haider Sami Salman; Sarah R. Nashee; Ahmed J. Shkarah (Journal of Emerging Science and Engineering, 2024)
The IEA's special study on CO2 collection, usage, and storage, released in 2020, estimates global CO2 capacity for storage to be among 8,000 and 55,000 gigatons. One of the most significant issues in introducing carbon into the energy market is improving carbon storage and developing more efficient distribution systems to increase the quantity of carbon that is held as liquid while decreasing storage pressure. The goal of this work is to investigate the efficiency of adsorption-based carbon-storing units from a "systems" perspective. The finite element approach, utilized in COMSOL Multi-physics™, is used to create an appropriate two-dimensional axisymmetric geometrical structure that balances energy, mass, and momentum based on thermodynamic extinction rules. We examine charging and discharging the storage unit with a rated pressure of 9 MPa and an initial temperature of 302 K.The storage tank is chilled using ice water. The research findings demonstrate that both simulated fluctuations in pressure and temperature during storage operations are extremely valuable. At the conclusion of charge time, the temperatures in the tank's center region are greater than those at the entry and along the wall, but at the end of discharge time, they are lower. The velocities are highest near the entry and progressively diminish throughout the tank's axis. As a result, even the lowest possible number (8,000 Gt) substantially surpasses the 100 Gt of CO2 required to be stored by 2055 under the "sustainable development" scenario. The IEA analysis also states that the land potential exceeds the offshore potential. Land-based storage capacity is estimated to be between 6,000 and 42,000 Gt, while offshore capacity is estimated to be between 2,000 and 13,000 Gt, assuming only sites less than 300 kilometers from the coast, at depths less than 300 meters, and outside the Arctic and Antarctic zones. Development of a prediction model to improve knowledge of a novel CO2 adsorbent during the adsorbent-desorption cycle, taking into account all transport events. Validation of the model against published data for H2 storage. Predicting pressure and temperature dispersion at various storage tank sites.